The Problem of Analytic Philosophy*. Issue 5 (September 2019) - Agassi, Joseph; Jarvie, Ian C.
Dainton and Robinson's Companion traces lines of descent of analytic philosophy from ancestors. They characterize analytic philosophy as a movement, a tradition, a style, and a commitment to the values of clarity and rigor. Critics of the ancestral movements and of analytic philosophy as such are conspicuous by their absence. The sociology of the spread of analytic philosophy is ventured, updating the original effort by Gellner.